Nestle ice cream in Cuba - Walker, Russell, 1972-; Bell, Kyle (London : SAGE Publications Ltd, 2017)
In 1996, as the Castro regime began welcoming limited international investment back to Cuba, Nestle signed a letter of intent with the Cuban government to build an ice cream factory in Havanas El Cotorro neighborhood. The plant, a joint venture between the Cuban government and Nestle, would produce high-quality ice cream products for tourists and affluent Cubans.Nearly twenty years after this decision to enter the Cuban market, it is not clear how successful the investment has been and what the future might hold for Nestle on the island. Nestle has faced important challenges in Cubasuch as supply shortages, entrenched domestic competitors, and risk of government interferencebut there has been evidence of some marketing and financial success. The 2015 normalization of diplomatic relations may bring new strategic threats and opportunities as American companies begin to eye the Cuban market and current competitors prepare for market changes.In the case, students will evaluate Nestles investment and strategy for future growth in the Cuban market and consider the companys market entry strategy, operations, and finances.
Originally published in Walker, R., & Bell, K. (2015). Nestle Ice Cream in Cuba. 5-315-504. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Nestle; International business enterprises -- Cuba; Ice cream industry -- Cuba